Performance evaluation of industrial systems : discrete event simulation in using Excel/VBA - Elizandro, David; Taha, Hamdy A., 1937- (CRC Press, 2012)
"Discussing fundamental modeling tools, queuing theory, and discrete event simulation for evaluating production systems, this book presents a development environment for discrete event simulation in a language easy enough to use but flexible enough to facilitate modeling complex systems. Incorporating the use of discrete simulation to statistically analyze a system and render the most efficient time-sequences, designs, upgrades, and operations, this new edition develops new visualization graphics for DEEDS software, includes improvements in the optimization of the simulation algorithms, and adds a chapter on queuing models"--Resumé vydavatele
Rev. vyd.: Simulation of industrial systems / David Elizandro. c2008
Keywords: modelování a simulace; simulační modely; počítačová simulace; operační výzkum; výrobní systémy; průmyslové inženýrství; modeling and simulation; simulation models; computer simulation; operations research; manufacturing systems; production engineering; monografie; monographs